EVALUATION OF PATIENT WITH SINONASAL MUCORMYCOSIS REFERED TO THE EAR, NOSE, AND THROAT (ENT) DEPARTMENT OF EMAM KHOMEINI HOSPITAL OF AHVAZ FROM 2001 UNTIL 2016 : Life Science-Surgery - ABSHIRINI, HASSAN; KAVEH, PEYMAN; JAVAD NAMAZI, MOHMMAD; MOHAMMAD EGHBALNEJAD MOFRAD, AMIR; KIANIZADEH, FATEMEH (International Journal of Life Science and Pharma Research, 2019)
Mucormycosis is an acute opportunistic infection which is caused by the most prevalent subgroup of mucoracae family, namely Rhizus oryazae. Mucormycosis infection could engage nose, paranasal sinuses, orbit and palate, as well as central nervous system. The fungi, when detected in the sinuses, could cause a wide range of diseases. The statistical population targeted in the present study includes the patients hospitalized during 2001 to 2016 in the ENT Department of Imam Khomeini Hospital (Ahvaz, Iran) who was diagnosed with mucormycosis of nose and sinus. This study is a review of hospital records containing patients’ information such as age, sex, underlying disease, engaged sinuses, and extent to the neighbor structures. In this study, 48 patients were examined. The highest prevalence of the disease is associated with palate which was found in 22 patients (45.83 percent). The second highest extent of prevalence was associated with orbit as it was found in 16 patients (31.25 percent). The lowest level of involvement was associated with central nervous system as it was solely diagnosed in 10 patients (20.83 percent). The highest numbers of patients were within the age range 51-70 years were male patiants. Diabetes was found to be the most prevalent underlying disease.